A comparison of menotropin, highly-purified menotropin and follitropin alfa in cycles of intracytoplasmic sperm injection - Schneider Danielle T; Verza Sidney; Schertz Joan C; Esteves Sandro C; Zabaglia Silval FC (BMC, 2009)
Abstract Background Over the last several decades, as a result of an evolution in manufacturing processes, a marked development has been made in the field of gonadotropins for ovarian stimulation. Initially, therapeutic gonadotropins were produced from a simple process of urine extraction and purification; now they are produced via a complex system involving recombinant technology, which yields gonadotropins with high levels of purity, quality, and consistency. Methods A retrospective analysis of 865 consecutive intracytoplasmic sperm injection (ICSI) cycles of controlled ovarian hyperstimulation (COH) compared the clinical efficacy of three gonadotropins (menotropin [hMG; n = 299], highly-purified hMG [HP-hMG; n = 330] and follitropin alfa [r-hFSH; n = 236]) for ovarian stimulation after pituitary down-regulation. The endpoints were live birth rates and total doses of gonadotropin per cycle and per pregnancy. Results Laboratory and clinical protocols remained unchanged over time, except for the type of gonadotropin used, which was introduced sequentially (hMG, then HP-hMG, and finally r-hFSH). Live birth rates were not significantly different for hMG (24.4%), HP-hMG (32.4%) and r-hFSH (30.1%; p = 0.09) groups. Total dose of gonadotropin per cycle was significantly higher in the hMG (2685 +/- 720 IU) and HP-hMG (2903 +/- 867 IU) groups compared with the r-hFSH-group (2268 +/- 747 IU; p < 0.001). Total dose of gonadotropin required to achieve clinical pregnancy was 15.7% and 11.0% higher for the hMG and HP-hMG groups, respectively, compared with the r-hFSH group, and for live births, the differences observed were 45.3% and 19.8%, respectively. Conclusion Although similar live birth rates were achieved, markedly lower doses of r-hFSH were required compared with hMG or HP-hMG.